Resistance of Clinical Strains of Pathogenic E.coli to Antibiotics and Bacteriophage in Hospitalized Children with Escherichiosis in St.Petersburg - N. V. Gonchar; I. V. Partina; O. I. Nyrkova; A. C. Drap (Антибиотики и Химиотерапия, 2020)
The data on the resistance frequency of the diarrheagenic E.coli isolates to antibacterial agents and a specific bacteriophage are presented. The strains were isolated from hospitalized children in St.Petersburg in 2011-2013 and belonged to three groups, i.e. enteropathogenic (EPE), enterotoxigenic (ETE) and enteroinvasine (EIE). It was shown that in the children aged from 1 month to 18 years the average antibiotic resistance was maximum in the EIE isolates and decreased in the following order: EIE (15.2%), EPE (6.0%), ETE (3.3%). The clinical EIE isolates showed no resistance to the new generation cephalosporins (cefuroxime, cephepime) and nitrofurans. The E.coli isolates of the three groups were characterized by high resistance to a specific bacteriophage which decreased in the following order: ETE (44.8%), EIE (37.0%), EPE (28.8%). The multiple resistance of the diarrheagenic E.coli isolates of the three groups to the antibacterials averaged 2.8%. The maximum frequency of resistance of the clinical isolates of the three groups to nalidixic acid was observed: EIE - 28.6%, EPE - 26.3%, ETE - 9.1%. The results of the study may be useful in the tactics of therapy of diarrheagenic E.coli infection in children.